2011
DOI: 10.1134/s0022476611060266
|View full text |Cite
|
Sign up to set email alerts
|

Contact angles as indicators of the polymer surface structure

Abstract: UDC 541:183:532.64The capacities of the wetting method for the characterization of the surface structure of polymers and surfactant adsorption layers on polymer surfaces and also the determination of the energy characteristics of polymer surfaces at different interfaces, which are used to optimize the choice of polymers in the solution of actual practical problems, are demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 14 publications
0
2
0
1
Order By: Relevance
“…The chemical composition of the PECVD membranes can directly affect their physico-chemical properties such as their hydrophobic/hydrophilic nature characterized from contact angle measurements. It can be justified by the fact that, hydrophily/hydrophoby properties depend on the membrane surface state and thus on the presence of active functions on the surface of the membrane [31], which will be investigated in part 3.3.…”
Section: Chemical Composition Of Pecvd Membranesmentioning
confidence: 99%
See 1 more Smart Citation
“…The chemical composition of the PECVD membranes can directly affect their physico-chemical properties such as their hydrophobic/hydrophilic nature characterized from contact angle measurements. It can be justified by the fact that, hydrophily/hydrophoby properties depend on the membrane surface state and thus on the presence of active functions on the surface of the membrane [31], which will be investigated in part 3.3.…”
Section: Chemical Composition Of Pecvd Membranesmentioning
confidence: 99%
“…Thus the pulsed discharge gives rise to more hydrophilic materials than the continuous one. This can be explained by the fact that the contact angle depends on the surface wettability, therefore on the roughness and the surface chemistry of the material [31]. Kale et al [32] demonstrated that the use of a pulsed plasma discharge made it possible to obtain more hydrophilic tetraethylorthosilicate and hexamethyldisiloxane polymers than those obtained in continuous plasma discharge from the same precursors because of the lower density and more organic nature of the materials obtained in pulsed synthesis conditions.…”
Section: Evaluation Of the Hydrophilic / Hydrophobic Character Of Pecvd Membranesmentioning
confidence: 99%
“…La humectabilidad es un parámetro importante en los materiales debido a que proporciona información sobre el comportamiento de su superficie (Marmur, 2006). En los materiales poliméricos este parámetro es útil para predecir el comportamiento que tendrán al estar en contacto con diferentes medios (Bogdanova et al, 2012).…”
Section: áNgulo De Contacto (Wca)unclassified